2017
DOI: 10.1016/j.pharmthera.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of tolerance and potential therapeutic interventions in Alopecia Areata

Abstract: This review aims to address the mechanisms of compromised immune tolerance contributing to the development and maintenance of Alopecia Areata (AA). Our goal is to also highlight future treatment opportunities and therapeutics that will safely and efficiently restore hair growth and maintain patients in remission. AA is a presumptive autoimmune disorder that coincides and genetically clusters to several other autoimmune diseases. In this review, we pay attention to the learnings from the mechanistic research an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 127 publications
0
18
0
Order By: Relevance
“…However, the association between alopecia areata and gut dysbiosis awaits to be elucidated. Alopecia areata may link with other autoimmune diseases, especially with IBD[30]. A series of clinical cases reported that hair loss was found in patients with IBD[31-34], with little knowledge of its causes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between alopecia areata and gut dysbiosis awaits to be elucidated. Alopecia areata may link with other autoimmune diseases, especially with IBD[30]. A series of clinical cases reported that hair loss was found in patients with IBD[31-34], with little knowledge of its causes.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of microbiome role in the autoimmune disease pathogenesis has been also contributed to microbial role immune mechanisms modulation . Several studies indicate that the loss of intestinal barrier integrity in local and systemic inflammation induction as well as autoimmunity . Literature data on the gastrointestinal role in AA indicate a higher prevalence of AA in patients with ulcerative colitis than in general population .…”
Section: Methodsmentioning
confidence: 95%
“…125 Several studies indicate that the loss of intestinal barrier integrity in local and systemic inflammation induction as well as autoimmunity. 126 Literature data on the gastrointestinal role in AA indicate a higher prevalence of AA in patients with ulcerative colitis than in general population. 127,128 Contradictory results were presented by Kim et al, 129 who observed no higher AA prevalence in the course of IBD.…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%
“…So far none of the traditional immunosuppressants and newer targeted treatments have been able to establish long‐lasting remission. This is attributed to the heterogeneous nature of the immune responses in AA, which cannot be targeted with a single agent, and the lack of anagen induction in the resting (catagen and telogen) HFs following restoration of IP …”
Section: Treatment Strategiesmentioning
confidence: 99%
“…This is attributed to the heterogeneous nature of the immune responses in AA, which cannot be targeted with a single agent, 193 and the lack of anagen induction in the resting (catagen and telogen) HFs following restoration of IP. 194 A number of suggestions have been made regarding future therapies, such as induction of peripheral tolerance in T cells, re-establishment of IP via administration of immune guardians, targeting the neuroendocrine-immune system and utilizing MIF ( Table 4, Fig. 4).…”
Section: Treatment Strategiesmentioning
confidence: 99%